Understanding Dietary Supplements - Hollenstein, Jenna (Book collections on Project MUSE., 2007)
For many consumers, taking one or more dietary supple-ments is a natural addition to a healthy lifestyle. The decision to take a dietary supplement may be based on the recommendation of a doctor, a dietitian, or a friend. Television, newspapers, magazines, websites, and persuasive marketing materials in the pharmacy or supermarket may sway buyers. Information regarding dietary supplements abounds but can be misleading or contradictory. Understanding Dietary Supplements is a guide to making informed choices. Chapters provide: Both an overview and detailed information about key supplements; Cove.